Global search for new physics with 2.0 fb(-1) at CDF - Aaltonen, T; Adelman, J; Akimoto, T; Albrow, MG; Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; et al. (2009)
Data collected in run II of the Fermilab Tevatron are searched for indications of new electroweak-scale physics. Rather than focusing on particular new physics scenarios, CDF data are analyzed for discrepancies with the standard model prediction. A model-independent approach (Vista) considers gross features of the data, and is sensitive to new large cross-section physics. Further sensitivity to new physics is provided by two additional algorithms: a Bump Hunter searches invariant mass distributions for "bumps" that could indicate resonant production of new particles, and the Sleuth procedure scans for data excesses at large summed transverse momentum. This combined global search for new physics in 2.0fb-1 of pp̄ collisions at s=1.96TeV reveals no indication of physics beyond the standard model. © 2009 The American Physical Society.